2015
DOI: 10.1021/ml5004553
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Novel AMPA Receptor Modulator through a Hybridization Approach

Abstract: ABSTRACT:The α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors are a family of glutamate ion channels of considerable interest in excitatory neurotransmission and associated disease processes. Here, we demonstrate how exploitation of the available X-ray crystal structure of the receptor ligand binding domain enabled the development of a new class of AMPA receptor positive allosteric modulators (7) through hybridization of known ligands (5 and 6), leading to a novel chemotype with promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A compilation of structures of fluorinated pyrazoles, their activities, and the corresponding references during the last 5 years are provided in Figure . …”
Section: Applications Of Fluorinated Pyrazolesmentioning
confidence: 99%
“…A compilation of structures of fluorinated pyrazoles, their activities, and the corresponding references during the last 5 years are provided in Figure . …”
Section: Applications Of Fluorinated Pyrazolesmentioning
confidence: 99%
“…Pfizer researchers also revealed a class of compounds known as dihydroisoxazoles (DHI), particularly hit 67 (Figure ), with apparent favorable physicochemical and ADME properties . Studies involving a hybridization strategy revealed structures such as compound 68 (Figure ), which showed significant in vivo biological activity against GluA2 …”
Section: Ampa Receptorsmentioning
confidence: 99%
“…[232] Studies involvingah ybridization strategy revealed structuress uch as compound 68 (Figure 7), which showeds ignificant in vivo biological activitya gainst GluA2. [233] Many more have been discovered in this context,a nd they are reviewed elsewhere. [217,226,234] What we stress herei st hat the evolution of studies relatedt ot argetingt he AMPAr eceptor is ag ood example of learning from failure.…”
Section: Ampar Eceptorsmentioning
confidence: 99%
“…A recent publication from one of the Organon authors currently working at the University of Strathclyde described another hybridisation strategy, [130] in which the hydroxymethyl pyrazole used in the design of 77 is combined with a template related to those previously described by Cortex to produce hybrid 79. Only in vitro activity data is de-scribed in an electrophysiology assay with compounds being tested on both flip and flop isoforms of GluA2.…”
Section: Optimization Of An Hts-derived Hit By Or-ganon Using Sbddmentioning
confidence: 99%